Argument and Verb Meaning Clustering From Expression Forms in LSE - García-Miguel, José M.; Cabeza-Pereiro, María del Carmen (Frontiers in Psychology, 2022)
Languages use predicates and arguments to express events and event participants. In order to establish generalizations concerning the variety languages show regarding the procedures to discern some arguments from the others, the concept of roles –and, particularly, macroroles, mesoroles and microroles- associated to participants provides a widely studied starting point. In this article, the formal properties in the arguments of a set of (meanings of) verbs in Spanish Sign Language have been analyzed. Arguments have been studied by considering their microroles and a quantitative method for measuring distances from a plurality of properties has been adopted. The novelty of this analysis is that it focuses on how arguments group in terms of these properties. Subsequently, some generalizations justifying why some verb meanings have a tendency to associate to certain forms of argument expression are hereby highlighted.